2016
DOI: 10.1142/s0218001416560024
|View full text |Cite
|
Sign up to set email alerts
|

A Palmprint Recognition Approach Based on Image Segmentation of Region of Interest

Abstract: To carry out an effective recognition for palmprint, this paper presents an algorithm of image segmentation of region of interest (ROI), extracts the ROI of a palmprint image and studies the composing features of palmprint. This paper constructs a coordinate by making use of characteristic points in the palm geometric contour, improves the algorithm of ROI extraction and provides a positioning method of ROI. Moreover, this paper uses the wavelet transform to divide up ROI, extracts the energy feature of wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Weizmann database is used to support this study which is shown in [39]. ese prior studies are cited at relevant places within the text as [1,2].…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Weizmann database is used to support this study which is shown in [39]. ese prior studies are cited at relevant places within the text as [1,2].…”
Section: Data Availabilitymentioning
confidence: 99%
“…Image segmentation aims to separate the "target" area and the "background" area of the input image and to extract the interesting part for in-depth understanding and analysis [1,2]. Segmented images are the advanced expression of the original pixels to semantic objects.…”
Section: Introductionmentioning
confidence: 99%